Politeness strategies used by Papuan students in virtual communication practices at university (Englisia : Journal of Language, Education, and Humanities, 2023)
This study aims at investigating and revealing language politeness strategies, as well as the factors that influence politeness strategies used by Papuan students during virtual in the context of virtual academic consultations as a practice of virtual communications to the lecturers. This study uses descriptive qualitative methods and purposive sampling to choose two lecturers and fifteen university students from the Papua as participants. Data was also gathered through online observation, offline interviews, and documentation. Online observations were made by evaluating screenshots of Google Classroom comments and recording of written conversations on WhatsApp and SMS sent by ten Papuan students. At the same time, offline interviews were carried out 10 students and 2 instructors. The data is then analysed using discourse analysis, which consists of multiple steps, including data recording, data transcription, data selection, and data interpretation. In line with the findings of this study, Papuan students use four types of politeness strategies when consulting with lecturers via virtual communication. They are positive, negative, bald on record, and off the record politeness strategies. In online communication, the negative politeness strategy is the most prevalent among Papuan students. The diversity of politeness strategies that are replicated, even if they appear unpleasant at times, is not an aspect of purposeful or disrespectful behaviour toward the interlocutor. But let us get back to the level of language skills, which still require more attention and are impacted by a variety of internal factors such as personality and age, and external factors such as culture, facilities obtained. The findings indicate that even when language capabilities are restricted in virtual communication, Papuan students receive enough education. This situation will improve the civility of language that students in Papua use while conversing digitally. As a result, higher education institutions in Papua should pay more attention to standard communication patterns when academic consulting with lecturers as speech partners in the context of higher education in Papua in order to develop comprehensive and effective communication practices.
Keywords: Virtual Communication Practices; Papuan Students; Politeness Strategy